IC-Technik zum Abheben. - Bruckner, Werner (Deutscher Verkehrs-Verl., 2006)
Technologien aller Art haben in den vergangenen Jahrzehnten die Globalisierung enorm beschleunigt und kräftig zur Steigerung des Flugaufkommens beigetragen. Nun setzen Unternehmen der Luftverkehrsbranche verstärkt Informations- und Kommunikationstechnik (ICT) ein, um ihre internen und übergreifenden Prozesse weiter zu optimieren und Kunden bessere Services zu bieten. difu

Will consumtion-driven transport continue growth? Transport forms an essential part of private consumption both directly and indirectly. The role it plays reflects both the development of household incomes and the way they are spent. The article identifies the amount of transport services that goes into the production and the final use of goods and services purchased by private households. Using input-output-techniques, it specifies transport intensities of different categories of household expenditure as well as the production sectors involved in satisfying consumer-induced transport demand. One of the main findings of this analysis is that the provison of transport services, including those rendered by the consumers themselves, accounts for about one-fifth of total consumer expenditure. It is against this background that the article investigates the effects consumer behaviour in an ageing society is likely to have on the growth of transport demand in the period up to 2020. difu difu
Keywords: Verkehr; Flughafen; Luftverkehr; Informationstechnologie; Kommunikationstechnologie; Flugsicherung; Wertschöpfung